Self development through scientific spirituality - PRAVIN KUMAR (Dev Sanskriti: Interdisciplinary International Journal, 2013)
In modern scientific age everything including the traditional spiritual practices get accepted only after proper evidence or logic is provided. Ācārya Śrīrām Śarmā had proposed scientific spirituality for evolution of every person; this contains four pillars (4S) Sādhanā, Swādhyāya, Saṁyam and Śevā. Individual development is the basis for the development of the society and the entire humankind. Citta is purifed by Sādhanā of Cāndrāyana practice. Manas is purifed by Swādhyāya (Self study). One can change  the muscular tension  while speaking from muscle tension level 10µV to 2-3µV in EMG reading. Saṁyam of speech for 3 months changes the brain wave pattern in occipital region and left hemisphere Broca's and Wernike's area. 4. Śevā (Service) comes only after self transformation; as according to Ācārya Śrī, Śānti Kunj is a nursery where people come and practice spirituality and cultivate good character; when they go back in the society they change it. These practices are not based on any specific religion, but instead they are for the entire human kind, as Ācārya Śrī set a goal of Yug Nirmān (transformation of the era). Since early 1970s, this nursery has been cultivating ideal human character. It is hoped that eventually an ideal human society will be formed; as one candle can light every other candle without losing anything.